Understanding and measuring morphological complexity - Baerman, Matthew; Brown, Dunstan; Corbett, Greville G. (Oxford University Press, 2015)
This work aims to assess the nature of morphological complexity, and the properties that distinguish it from the complexity manifested in other components of language. Chapters highlight novel perspectives on conceptualizing morphological complexity, and offer concrete means for measuring, quantifying and analysing it